Intracerebroventricular MOTS-C Infusion Increases Peripheral Uncoupling Proteins in Rats Generated From Experimental Obesity Model - Tekin, Suat; Onalan, Ebru Etem; Sandal, Suleyman (Wiley, 2019)
[Abstract Not Available]
Keywords: MOTS-c; UCP1; UCP3; obesity; infusion